The The Correlation of Neutrophil-to-Lymphocyte Ratio with LupusQoL in Systemic Lupus Erythematosus Patients - Mahrunnisa Rienti Sepestian; Lipinwati; Dewi, Hasna; Hanina; Nyimas Natasha Ayu Shafira (Journal of Medical Studies, 2025)
Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease with diverse clinical manifestations depending on disease activity. Clinical manifestations, disease activity, and side effects of treatment can affect quality of life. The LupusQoL questionnaire assesses the disease's impact on eight quality of life domains. The Neutrophil-to-Lymphocyte Ratio (NLR) is an inflammatory biomarker that correlates with SLE disease activity. Objective: This research aims to determine the correlation between NLR and various domains of the LupusQoL questionnaire in SLE patients. Methods: This observational analytic study used purposive sampling, involving 32 SLE patients treated at Raden Mattaher Hospital, Jambi, in 2024. NLR was obtained from blood counts performed within the last 4 weeks, and HRQOL was measured using the LupusQoL questionnaire. Data were analyzed using Pearson correlation. Result: The mean NLR was 6.50 (1.3–29.43). LupusQoL showed the lowest score in fatigue (58.85). Pearson analysis revealed a moderate inverse correlation between NLR and the planning domain of LupusQoL (p= 0,022). NLR shows no statistically significant correlation with physical health, pain, intimacy, burden to others, emotional health, body image, or fatigue in SLE patients, as p-values >0.05. Conclusion: Higher NLR is correlated with lower planning domain HRQoL in SLE patients and vice versa.